Chemomechanical Motion of a Self‐Oscillating Gel in a Protic Ionic Liquid. Issue 51 (20th November 2018) - Masuda, Tsukuru; Ueki, Takeshi; Tamate, Ryota; Matsukawa, Ko; Yoshida, Ryo
Abstract: An autonomous swelling–deswelling oscillation of polymer gels in a hydrated protic ionic liquid (PIL) as a proton source for the Belousov–Zhabotinsky (BZ) reaction is presented. Methylammonium hydrogen sulfate ([maH + ][HSO4 − ]) was employed as the PIL because it provides stable redox oscillation in the BZ reaction. Due to the significantly higher p K a for [maH + ][HSO4 − ] than those for conventional proton sources for the BZ reaction, chemomechanical oscillation can be expected under weaker acidic conditions. The self‐oscillating polymer was designed as a ternary random copolymer of N ‐isopropylacrylamide, N ‐(3‐aminopropyl)methacrylamide, and the Ru(bpy)3 moiety as a catalyst for the BZ reaction. The copolymer exhibited spontaneous soluble–insoluble oscillation in hydrated [maH + ][HSO4 − ] containing NaBrO3 and malonic acid. Macroscopic swelling–deswelling oscillation of the porous bulk gel prepared by covalently connecting microgel particles was also observed. Abstract : An autonomous swelling‐deswelling oscillation of polymer gels was achieved in a hydrated protic ionic liquid (PIL) as a proton source for the Belousov–Zhabotinsky (BZ) reaction. The PIL acts as a medium for the BZ reaction and is a promising material for developing self‐oscillating gels under milder conditions.